Reforma al Còdigo de la Niñez y Adolescencia, en cuanto al premio personal a los obligados subsidiarios al pago de pensiones alimenticias - Flores Obando, Edison Cornelio (2016)
The theme chosen for this thesis states: "REFORM CODE OF CHILDHOOD AND ADOLESCENCE, WITH RESPECT TO THE REQUIRED PERSONAL urged SUBSIDIARY TO alimony payments" were raised in the same objective "Make a legal, doctrinal critical to Code for Children and Adolescents and the required personnel urgently subsidiary of maintenance under Ecuadorian law. "Similarly, the hypothesis states "The urgency to the solidarity of maintenance, violates the constitutional principle that no one shall be deprived of his liberty by debt." To get to check each of these expressions, I conducted a literature that formed the basis for research in the same field which obtained the views of legal professionals who are able to establish the conclusion that the pressure required to staff solidarity to pay alimony in cases of fulfilling this responsibility, it is a legal aberration which violates the rights of individuals, including the right to liberty, and who gives a responsibility that should not competent. It is understood therefore that research under a deep doctrinal legal analysis, enjoys the validity and reliability criteria of lawyers with extensive experience provided me, to finally present the conclusions, recommendations and legal reform to Code children and Adolescents, which I propose as an alternative solution to this problem.